2014
DOI: 10.1152/jn.00295.2014
|View full text |Cite
|
Sign up to set email alerts
|

Eating interrupted: the effect of intent on hand-to-mouth actions

Abstract: Flindall JW, Gonzalez CL. Eating interrupted: the effect of intent on hand-to-mouth actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…This task difference in hand pre-shaping is predominantly lateralized to the right hand, regardless of a person's overall hand preference (Flindall and Gonzalez, 2013 ; Flindall et al, 2014 ). Taken together, these findings all support a theory of human motor cortex organized around a catalog of movements based on end-goal, rather than mechanical requirements (Graziano et al, 2002 , 2004 , 2005 ; Fogassi et al, 2005 ; Graziano, 2006 , 2009 ; Bonini et al, 2011 , 2012 ; Flindall and Gonzalez, 2013 , 2014 ). The results from the present study demonstrating greater right-hand use for the grasp-to-eat task further support the proposal that this type of action might be at the forefront of population level right-handedness in humans.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This task difference in hand pre-shaping is predominantly lateralized to the right hand, regardless of a person's overall hand preference (Flindall and Gonzalez, 2013 ; Flindall et al, 2014 ). Taken together, these findings all support a theory of human motor cortex organized around a catalog of movements based on end-goal, rather than mechanical requirements (Graziano et al, 2002 , 2004 , 2005 ; Fogassi et al, 2005 ; Graziano, 2006 , 2009 ; Bonini et al, 2011 , 2012 ; Flindall and Gonzalez, 2013 , 2014 ). The results from the present study demonstrating greater right-hand use for the grasp-to-eat task further support the proposal that this type of action might be at the forefront of population level right-handedness in humans.…”
Section: Discussionsupporting
confidence: 71%
“…This presumption is supported by findings from Sacrey et al ( 2013 ), who found that children develop a right-hand preference for grasp-to-eat tasks several years earlier than they do for grasp-to-build tasks. Furthermore, Flindall and Gonzalez (Flindall and Gonzalez, 2013 , 2014 , submitted; Flindall et al, 2014 ) have found a left-hemisphere/right-hand advantage in the kinematics of grasp-to-eat/hand-to-mouth actions that is absent from grasp-to-place actions. Specifically, when grasping a small food item with intent to eat, participants produce tighter maximum grip apertures during the outgoing movement than when grasping the same item to place it in a receptacle near the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been described in 1-to 5-year-old children: right-hand preference for grasp-to-eat movement was present earlier (from 1 year of age) and was then stronger than hand preference for grasp-to-build movement (Sacrey et al, 2013). However, although mechanical requirements of the different types of grasp do seem identical, investigations of hand kinematics have shown smaller grip apertures during the pre-shaping phase of right-hand grasp-to-eat action, compared to other grasping movements (Flindall and Gonzalez, 2014). Smaller grip apertures are typically associated with greater precision, in relation with increased need for visual and somatosensory guidance of the hand, which might explain the greater right-hand bias for reachto-eat behavior.…”
Section: Grasping and Manipulating Objectsmentioning
confidence: 96%
“…Our finding that hand preference for the grasp-to-eat action is a reliable predictor of the proficiency of speech articulation provides support for the speculation that the hand to mouth action, which developed for ingestion, may also subserve vocal communication (Gentilucci et al, 2009; Flindall and Gonzalez, 2013). Moreover, the grasp-to-eat action has been shown to be lateralized to the left hemisphere (Flindall and Gonzalez, 2013, 2014; Flindall et al, 2014). Specifically they have shown a right hand advantage in the kinematics of grasp-to-eat/hand-to-mouth actions that is absent from grasp-to-place actions.…”
Section: Discussionmentioning
confidence: 99%